THE USE OF DICTATION METHOD IN ENGLISH WRITING ACHIEVEMENT AT SMP NEGERI 31 PALEMBANG - Putry Desi Lestari; Herlina; Ana Theriana (Esteem Journal of English Education Study Programme, 2024)
This study examined the implementation and effectiveness of the Dictation Method in enhancing English writing achievement among seventh-grade students at SMP Negeri 31 Palembang. The research addressed two main questions: first, how students respond to the Dictation Method in their English learning; and second, how teachers implemented this method in classroom practice. Data were collected through surveys administered to 132 students across four classes, employing Likert scale analysis to gauge student perceptions. Results indicated overwhelming student approval (96%) of the Dictation Method, This study examined the implementation and effectiveness of the Dictation Method in enhancing English writing achievement among seventh-grade students at SMP Negeri 31 Palembang. The research addressed two main questions: first, how students respond to the Dictation Method in their English learning; and second, how teachers implemented this method in classroom practice. Data were collected through surveys administered to 132 students across four classes, employing Likert scale analysis to gauge student perceptions. Results indicated overwhelming student approval (96%) of the Dictation Method.